Comparing the effectiveness between issr and ssr markers in assessing genetic diversity of natural populations of Dacrydium elatum in Tay Nguyen, Vietnam - Liễu, Trần Thị; Hiền, Vũ Thị Thu; Liễu, Nguyễn Thị; Phòng, Đinh Thị (Vietnam Journal of Biotechnology, 2018)
The two techniques, ISSR (27 markers) and SSR (20 markers), were used to compare the effectiveness and to assess genetic diversity of 70 Dacrydium elatum samples collected in Lam Dong, Kon Tum, Dak Lak, and Gia Lai. The results showed 38/47 polymorphic markers (23/27 ISSR and 15/20 SSR markers) and 180 amplified DNA fragments, in which 85/127 (66.93%) and 46/53 (86.79%) were polymorphic for ISSR and SSR markers, respectively. Generally, the average values among the genetic diversity parameters of the populations for SSR (Hj = 0.213; Ne = 1.566, I = 0.444; He = 0.301; h = 0.228; and PPB = 72.50%) were higher than those for ISSR (Hj = 0.155; Ne = 1.142, I = 0.125; He = 0.083; h = 0.074 and PPB = 25.07%). The correlation coefficient between genetic distance measured with ISSR and combining ISSR + SSR was higher (r = 0.92) than that measured with SSR and combining ISSR + SSR (r = 0.65). There was not much difference in the total level of molecular variance (AMOVA) among populations and among individuals when analyzing ISSR and SSR data separately or combining both data. The three dendrograms constructed based on similarity matrix generated by ISSR, SSR and ISSR + SSR data were similar and they all divided the 70 D. elatum samples into two main groups with genetic similarity coefficients ranged from 74 to 99%, 78.4 to 100% and 76 to 96.6%, respectively. The obtained results indicated D. elatum species should be protected at the population level